Determinants of Purchase Intention toward Safi Halal Cosmetics in Indonesia - Fatkhurrokhman, Tiyan; Anggoro, Wisanggeni Bagus; Akbar, Tian Khusni; Azizah, Zaezah Nisa (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2026)
The development of the halal cosmetics industry in Indonesia has shown significant growth in line with the increasing awareness of Muslim consumers regarding halal aspects, ethical values, and product conformity with Islamic teachings. However, consumer purchase intention toward halal cosmetics is not determined solely by halal certification, but also by symbolic and psychological factors embedded in the brand. This study aims to analyze the influence of Halal Brand Image, Islamic Brand Personality, and Religiosity on consumer purchase intention for Safi halal cosmetic products in Indonesia. A quantitative approach with an explanatory research design was employed. Primary data were collected through an online survey using a structured questionnaire administered to 100 Muslim respondents who are familiar with or interested in Safi products, using purposive sampling techniques. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that Halal Brand Image, Islamic Brand Personality, and Religiosity have a positive and significant effect on consumer purchase intention, both partially and simultaneously. The research model is able to explain a substantial portion of the variation in consumer purchase intention, confirming that halal cosmetic consumption is influenced by a combination of brand image, Islamic brand personality, and consumer religiosity. This study concludes that halal cosmetic marketing strategies should emphasize strengthening brand identity that is authentic and aligned with Islamic values to enhance Muslim consumers’ purchase intention in Indonesia.